2014
DOI: 10.1111/1467-8489.12063
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and farm size inAustralian agriculture: reinvestigating the returns to scale

Abstract: A positive relationship between farm size and farm productivity is often considered to be largely due to increasing returns to scale in farm production. However, using farmlevel data for the Australian broadacre industry, we found that constant or mildly decreasing returns to scale is the more typical scenario. In this study, the marginal returns to various farm inputs are compared across farms with different sizes. We found that large farms achieved higher productivity by changing production technology rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 21 publications
2
43
2
3
Order By: Relevance
“…A factor productivity can be improved by its scale of use (economies of scale), but the increase in farm size may also unlock opportunities to capitalize on new techniques, technologies and practices that can improve productivity (economies of size). This distinction between economies of size and economies of scale (Hallam, 1991) supported the rationale that smaller farms were more likely to gain competitiveness by investing to improve their technical efficiency (adopting good technologies and/or practices) rather than by increasing their size (Sheng et al, 2014;Singbo and Larue, 2014). The evidence from our beef cattle farms suggested that the increase in size had entailed taking on equipment and organizational practices (fully mechanized forage harvesting and distribution chain) that had no effect on productivity (no economies of size), which had incentivized the farmers to grow bigger in a move to amortize these new technologies (economies of scale).…”
Section: Discussionmentioning
confidence: 90%
“…A factor productivity can be improved by its scale of use (economies of scale), but the increase in farm size may also unlock opportunities to capitalize on new techniques, technologies and practices that can improve productivity (economies of size). This distinction between economies of size and economies of scale (Hallam, 1991) supported the rationale that smaller farms were more likely to gain competitiveness by investing to improve their technical efficiency (adopting good technologies and/or practices) rather than by increasing their size (Sheng et al, 2014;Singbo and Larue, 2014). The evidence from our beef cattle farms suggested that the increase in size had entailed taking on equipment and organizational practices (fully mechanized forage harvesting and distribution chain) that had no effect on productivity (no economies of size), which had incentivized the farmers to grow bigger in a move to amortize these new technologies (economies of scale).…”
Section: Discussionmentioning
confidence: 90%
“…They also suggest that large agricultural farms that have been engaged in cropping gain an advantage from the use of technologies. Sheng et al (2014), however, note that larger firms achieved higher productivity not by increasing their scale but by changing production technology. The precise nature of the mapping from ICTs to agricultural revenue (outputs) is the subject of the following section.…”
Section: Introductionmentioning
confidence: 98%
“…Since 1978, the number of Australian broadacre agriculture farms decreased by one quarter, while average farm size (measured by the gross value of output per farm in real terms) nearly doubled. Moreover, the top 20 per cent of farms now account for more than half of total output as market share and input use shift towards fewer, larger farms (Sheng et al 2015).…”
Section: Introductionmentioning
confidence: 99%